Variabilitas ENSO terhadap Arus Pusaran dan Sebaran Ikan Cakalang di Wilayah Pengelolaan Perikanan 713 - Ratnasari, Syarifah Leila; Harahap, Syawaluddin; sunarto, sunarto; Purba, Noir; Pranowo, Widodo (Jurnal Harpodon Borneo, 2017)
The Fisheries Management Area (WPP) RI KP 713 under Decree No. 1 year 2009 includes Makassar Strait, Bone Bay, Flores Sea and the Sea of Bali. WPP-RI 713 is an area traversed by Arlindo. Arlindo occurs due to differences in surface pressure between the Pacific and Indian Oceans that value varies and it is influenced by the ENSO (Gordon et al, 2008). ENSO criteria can affect eddies variations. Eddies can affect the value SPL and salinity will affect the distribution of skipjack fish. This study aimed to analyze the relationship of ENSO variability with eddy patterns and biomass skipjack in 2014 - 2016. The research method was conducted descriptively by visualizing the variability of ENSO and skipjack biomass in the graph. Meanwhile, visualization current distribution patterns, SPL, and salinity using the ODV software. The relationship between all the variables are calculated by linear regression quantitatively. The visualization results indicate ENSO criteria affects eddy patterns, temperature, and salinity. By the time El Nino years of 2014 - 2015 occured 10-12 eddies, SPL average colder 290C, and higher salinity 33.3 psu. In 2016 a normal year with decreased eddies 9 incident, SST average 30.2oC, and salinity 33.3 psu. Distribution of Skipjack showed significant patterns between phases Nino years of 2014 - 2015 with the average 2.75 – 3.25 g/m2 and a normal year with the average 9:15 g / m2. Linear correlation between ENSO and the current showed positive results in 2014 and 2016, whereas in 2015 was negative. The correlation between ENSO and skipjack biomass showed positive results in 2015 and 2016, whereas in 2014 was negative.Keywords : ENSO, Eddy, Skipjack Biomass, Temperature, Salinity